Chiral Luminescent Liquid Crystal with Multi‐State‐Reversibility: Breakthrough in Advanced Anti‐Counterfeiting Materials. Issue 20 (1st May 2022) - Shi, Yonghong; Han, Jianlei; Jin, Xue; Miao, Wangen; Zhang, Yi; Duan, Pengfei
Abstract: Creating a security material that carries distinct information in reflective color, fluorescence, and chiroptical property will enhance anti‐counterfeiting levels to deter counterfeits ranging from currencies to pharmaceuticals, but is proven extremely challenging. In this work, an advanced anti‐counterfeiting material, with three‐state of each mode reversibly converted into multi‐mode materials including reflective color, fluorescence, and circularly polarized luminescence signal, is constructed by loading photofluorochromic spiropyran (SP) and zinc ion (Zn 2+ ) into the chiral liquid crystal. Under UV irradiation, the complexes of SP and Zn 2+ will be transformed into merocyanine (MC) and MC‐Zn 2+, while the energy transfer occurs from MC‐Zn 2+ to MC. Upon heating, MC is easy to recover to SP, while the MC‐Zn 2+ remains unchanged. The MC and MC‐Zn 2+ can be transformed into the SP and Zn 2+ under visible light irradiation. The three states of each mode can reversibly convert. Furthermore, the reflective color or fluorescence of each state shows different intensities under left‐ and right‐handed circular polarized filters, enabling easy distinguishing by naked eyes. The advanced anti‐counterfeiting method with multi‐state of each mode for multi‐mode encryption information output will provide a new concept for designing and fabricating multi‐mode anti‐counterfeiting materials, improving the security level for practical application. Abstract : Advanced anti‐counterfeiting material has multi‐mode information outputs including reflective color, fluorescence, and circularly polarized luminescence signal. Each mode has three states, and the three‐state information can be reversibly converted. Assisted by the left‐ and right‐handed circular polarized filters, the intensity of reflective color and fluorescence of each state can be distinguished by the naked eye.